NOTES ON THE ALL-RUSSIAN SEMINAR «CURRENT OBJECTIVES IN FORENSIC VEHICLE EXAMINATION: CONDUCTING VEHICLE INSPECTION TO ESTIMATE THE COST OF AUTOMOTIVE REPAIR AND RESTORATION AND FOR THE PURPOSES OF VEHICLE VALUATION» - S. Fedotov (Теория и практика судебной экспертизы)
.